Do Bedside Handovers Reduce Handover Duration? An Observational Study With Implications for Evidence‐Based Practice. Issue 6 (15th October 2018) - Malfait, Simon; Van Hecke, Ann; Van Biesen, Wim; Eeckloo, Kristof
Abstract: Introduction: Bedside handover is increasingly used and studied in nursing due to the method's acclaimed positive effects on patient safety, patient participation, communication, and efficiency. Still, reported results about its impact on handover duration are ambiguous. Revealing the root cause of these ambiguous effects is important, as increased duration could lead to overtime, lower job satisfaction, and failure in implementation. In contrast, decreased handover duration could lead to more efficient nursing care and facilitate implementation. Aim: To explore the effects of bedside handovers on the handover duration by comparing wards before and after the implementation of bedside handovers. Methods: As part of a multicentered longitudinal study, observations ( N = 638) with time measurement were performed. Approximately 22% of the observations were performed by two researchers to check reliability. These time measurements were compared to the handover duration before the implementation of bedside handover, determined through interviews ( n = 105), unstructured observations ( n = 40), and a review of time schedules ( n = 12). A descriptive, comparative research design was used. Results: On average, a bedside handover takes 146 s for one patient (83 s–204 s). Depending on the previously used handover model, the number of patients allocated to each nurse, and the use of a structured handover content, time gain or loss as a result of introducing the bedside handover can be expected. Linking Evidence to Action: The effect on time depends on the organizational changes necessary for the implementation of bedside handovers, most importantly the use of a decentralized handover model and structured handover content. Implementing bedside handover will therefore not always lead to a decrease in time use. A matrix for estimating the effects of bedside handover on time use is presented. While using bedside handovers will not always lead to decreased handover time, it will increase direct patient contact, increasing the possibilities for patient participation and enhancing patient safety.